EFEKTIVITAS IMPRESION MANAGEMENT ANIES BASWEDAN SEBAGAI CAPRES 2024 TERHADAP SIKAP PEMILIH PEMULA - Hayati, Sagita Rahma (Jurnal Media dan Komunikasi Indonesia, 2025)
Anies Baswedan is a political figure who plays a role, in this case political public relations is very important for carrying out impression management, especially ahead of the 2024 presidential election. The purpose In this study, was to find what kind the impression management strategies Anies Baswedan used through his Instagram account @aniesbaswedan during the 2024 presidential election campaign. This study is using a quantitative method with a positivism paradigm by distributing questionnaires to respondents who are followers of Anies Baswedan's Instagram account and also beginner voters aged 17-21 years. The subject and object in this research are Anies Baswedan as the object and followers as the subject. The population in this study are followers of Instagram account @aniesbaswedan. And the results of this study are show that the strategy most often likely to perform by Anies Baswedan is the ingratiation strategy, Anies wants to get the impression of being a 2024 Presidential candidate who wants to be liked by sympathetic actions.